Объяснение:= b2 - 4ac = 92 - 4·2·10 = 81 - 80 = 1
x1 = -9 - √1 2·2 = -9 - 1 4 = -10 4 = -2.5
x2 = -9 + √1 2·2 = -9 + 1 4 = -8 4 = -2
D = b2 - 4ac = 172 - 4·1·0 = 289 - 0 = 289
x1 = -17 - √289 2·1 = -17 - 17 2 = -34 2 = -17
x2 = -17 + √289 2·1 = -17 + 17 2 = 0 2 = 0
D = b2 - 4ac = 82 - 4·5·(-4) = 64 + 80 = 144
x1 = -8 - √144 2·5 = -8 - 12 10 = -20 10 = -2
x2 = -8 + √144 2·5 = -8 + 12 10 = 4 10 = 0.4
D = b2 - 4ac = (-2)2 - 4·7·(-14) = 4 + 392 = 396
x1 = 2 - √396 2·7 = 1 7 - 3 7 √11 ≈ -1.2785534815808857
x2 = 2 + √396 2·7 = 1 7 + 3 7 √11 ≈ 1.5642677672951713
= b2 - 4ac = (-7)2 - 4·1·12 = 49 - 48 = 1
x1 = 7 - √1 2·1 = 7 - 1 2 = 6 2 = 3
x2 = 7 + √1 2·1 = 7 + 1 2 = 8 2 = 4
3.68. a) -2;0. 3;5.
б) -10; -6. -1;3.
3.69. а) -5;25. 3;9.
б) 1;-17. -1;-17.
Объяснение:
подстановки.
a) x^2-y=4; (1)
y=x+2; (2)
(2) подставляем в (1)
x^2 - (x+2)=4;
x^2-x-2-4=0;
x^2-x-2-4=0;
x^2-x-6=0;по т. Виета
x1+x2=1;
x1*x2=-6;
x1=-2; x2=3.
x1=-2 подставляем в (2)
y=-2+2;
y1=0;
x2=3 подставляем в (2)
y=3+2;
y2=5.
б) x=y-4; (3)
y^2+3x=6; (4)
(3) подставляем в (4):
y^2+3(y-4)=6;
y^2+3y-12=6;
y^2+3y-12-6=0;
y^2+3y-18=0;
по т. Виета
y1+y2=-3; y1*y2=-18;
y1=-6; y2=3.
y1=-6 подставляем в (3)
x=-6-4;
x1=-10;
y2=3 подставляем в (3)
x=3-4;
x2=-1.
сложения.
а) x^2-y=0; (5)
2x+y=15; (6)
Складываем (5) и (6):
x^2+2x=15;
x^2+2x-15=0;
по т. Виета
x1+x2=-2; x1*x2=-15;
x1=-5; x2=3;
x1=-5 подставляем в (6):
2(-5)+y=15;
-10+y=15;
y=15+10;
y1=25;
x2=3 подставляем в (6):
2*3+y=15;
6+y=15;
y=15-6;
y2=9.
б) x^2-y=18; (7)
x^2+y=-16; (8)
Складываем (7) и (8):
x^2 + x^2=18+(-16);
2x^2=2;
x^2=1;
x1,2=±1;
x1=1 подставляем в (7)
1^2-y=18;
-y= 18-1;
y1= -17;
x=-1 подставляем в (7)
(-1)^2-y=18;
1-y=18;
y2=-17.